DEVELOPMENT OF ALTERNATIVE ENERGY IN UKRAINE: THE MODERN STATE AND EFFECTIVENESS OF MACHINERIES OF THE STATE ADJUSTING - Voloshin O.L. (Pressing Problems of Public Administration, 2015)
The modern state and problem aspects of development of alternative energy is analysed in Ukraine. Effectiveness of machineries of the state adjusting and potential of development of alternative energy is definite in Ukraine.